The EGOIN theory : an analysis of Sub-Saharan Africa (1996-2006). - Le, Thu Hoai. (2008)
Despite having had more than three decades of independent public policy, some countries in Sub-Saharan Africa (SSA) continue to be severely under-developed with growth rates of less than 2% during the period 1996–2006. It is the purpose of our study to examine the cross-country effects of five factors – Entrepreneurship, Government, Ordinary Labor, Investment and Natural resources (known as the EGOIN theory) on GDP per capita covering forty-seven countries in SSA. In addition, we attempt to improvise EGOIN theory by introducing the impacts of the other three most eminent factors such as ODA, external debt and civil wars into our study. To see if these factors can explain the relatively low GDP per capita in the SSA countries, we apply Fixed-Effects (FE) and Random-Effects (RE) estimation techniques to a set of data spanning the period of 1996–2006. We ask the following questions: What are the impacts of EGOIN factors, ODA per capita, external debt per capita and civil wars have on GDP per capita? To what extent do these factors contribute to GDP per capita? Which factor sees the highest GDP per capita? Lastly, what are the salient implications for data and policy work? The results obtained in our regressions are somewhat disappointing: RL and existence of war fail to enter significantly in the determination of economic growth at the 10% level, although their signs are as expected. On the other hand, ODA per capita, FDI per capita and external debt per capita exhibit significant impact on GDP per capita at 10% level, with FDI per capita having the greatest impact on GDP per capita. Based on our empirical findings and results, in order for the region as a whole to break away successfully from the low income group classification’, we strongly feel that good governance is the key solution to this problem.